Dominasi Harga dan Promosi serta Inovasi Produk terhadap Keputusan Pembelian Smartphone Merek Vivo - Sudarsana, Putu Agus Eka; Yulianthini, Ni Nyoman (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This study aims to examine (1) the effect of prices on purchasing decisions (2) the effect of promotion on purchasing decisions (3) the effect of product innovation on purchasing decisions (4) the influence of jointly price, promotion, and product innovation on purchasing decisions. This research is included in research with a causal quantitative approach. The subjects in this study were students of the Faculty of Economics, Ganesha University of Education who had used Smartphone products from the Vivo brand and other brands in the past 1 year. The objects in this research are price, promotion, and product innovation and purchasing decisions. This study used a sample of 75 respondents. Data were collected using a questionnaire instrument that has a total of 15 statements, then the data obtained were analyzed using multiple linear regression analysis. The results of this study indicate that (1) price has a positive and significant effect on purchasing decisions (2) promotion has a positive and significant effect on purchasing decisions (3) product innovation has a positive and significant effect on purchasing decisions (4) prices, promotions, and product innovations together have a significant effect on the decision to purchase a Vivo smartphone.